Revitalization of Disaster Management System in GBKP Klasis Sinabun towards Resilience of Mount Sinabung Survivors Community - Eikel Karunia Ginting (Jurnal Teologi Pambelum, 2024)
This paper analyzes the disaster management system in GBKP Klasis Sinabun which is closely related to the presbyterial-synodal system. This system has vulnerabilities due to the slow handling of disasters due to presbyterial decisions (elders) and the role of the synodal (center).  In analyzing the context of the problem, the author uses the theory of resilience and human security to see the problems and challenges that exist in fulfilling the security of the community around Sinabung. The theory of resilience and human security also provides an evaluation for holistic disaster management to have a vital impact between GBKP Klasis Sinabun and the community around Sinabung. This research uses a literature approach, and descriptive analysis method combined with interviews.